2019
DOI: 10.1111/iwj.13128
|View full text |Cite
|
Sign up to set email alerts
|

Negative pressure wound therapy as a definitive treatment for upper extremity wound defects: A systematic review

Abstract: Negative pressure wound therapy (NPWT) represents one of the many solutions for complex wounds of the upper extremity. The goal of this study was to investigate the most common indications for definitive treatment of wound defects in the upper extremity with NPWT and to report revision surgery outcomes after its use. A systematic review of the literature was performed. The following keywords and their combinations were used: "upper extremity," "arm," "forearm," "wrist," "hand," "finger" AND "negative-pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…NPWT has been applied to various surgical wounds since 1997 [ 135 ]. It can accelerate wound healing on both acute and chronic wounds, and it has been widely used on wounds with soft tissue defects [ 136 , 137 ]. Although the mechanism of NPWT promoting wound healing is not fully understood, some researchers suggest that it may contribute to maintaining a moist environment for wounds, removing inflammatory exudate from the wound, and reducing exposure to pathogens [ 138 , 139 ].…”
Section: Surgical Approachesmentioning
confidence: 99%
“…NPWT has been applied to various surgical wounds since 1997 [ 135 ]. It can accelerate wound healing on both acute and chronic wounds, and it has been widely used on wounds with soft tissue defects [ 136 , 137 ]. Although the mechanism of NPWT promoting wound healing is not fully understood, some researchers suggest that it may contribute to maintaining a moist environment for wounds, removing inflammatory exudate from the wound, and reducing exposure to pathogens [ 138 , 139 ].…”
Section: Surgical Approachesmentioning
confidence: 99%
“…Negative pressure wound therapy (NPWT) has become a valuable aid to the management of complex wounds of the upper extremity (Shine et al, 2019). The mechanism of action of NPWT is attributed to an increase of local blood flow, the promotion of angiogenesis, removing excessive fluid and bacterial load, the induction of cellular proliferation accelerating tissue regeneration and approximating the wound edges, so reducing the wound surface area (Moue ¨s et al, 2011).…”
Section: Emerging Methods and Applicationmentioning
confidence: 99%
“…In the last decade, negative pressure wound therapy (NPWT) efficacy emerged, simplifying management of wound complications and avoiding more complex surgical procedures. A recent review 42 including 404 upper extremities cases, reported good results in 90% of cases, highlighting that NPWT could be considered not only a temporary management tool but even a definitive treatment in selected patients. Minor and some major wound complications are nowadays best treated with oral antibiotics associated with NPWT: this treatment can resolve the majority of cases, often avoiding premature hardware removal.…”
Section: Wound Complications and Infectionsmentioning
confidence: 99%